Efficiency of money laundering countermeasures: Case studies from European Union Member States - Corina-Narcisa Cotoc; Maria Nițu; Mircea Constantin Șcheau; Adeline-Cristina Cozma (Risks, 2021)
The aim of this study is to present the trends and effectiveness of money laundering countermeasures from the perspective of a number of suspicious transactions reported to the Financial Intelligence Units (FIUs), a number of analysis results submitted to law enforcement authorities, and the typologies of cases in European Union Member States. In order to determine the impact of the joint effort in the fight against money laundering, we used descriptive statistics to process the data and case studies from annual reports of the European FIUs for 2018 and 2019. The results of our study highlight the increase in the number of suspicious transactions notices, as well as in their quality level. There is an increasing tendency towards information exchange between European Union countries regarding the suspicion of money laundering, but there is no stable trend for referring cases to law enforcement and other responsible institutions. Based on the available data, it can be concluded that the EU anti money laundering measures are efficient, but further steps are needed to achieve higher international coordination and cooperation.
Keywords: 330; anti money laundering; EU directives; efficiency; Financial Intelligence Units